(untitled) (Bangladesh Journal of Medical Science, 2020)
Background: Birth weight of an infant is the most important determinant of its chances of survival, healthy growth, and development. It depends on many maternal factors. Maternal age, parity and gestational age have been shown to increase the risk of adverse neonatal outcome, such as intrauterine growth retardation, prematurity, mortality and low birth weight. Objective: This study was planned to observe the incidence of low birth weight baby and to correlate the maternal age, parity and gestational age on birth weight of babies. Methodology: It was a retrospective study. Data were collected from medical records. Total 2850 live births new born baby were enrolled in this study during the period January 2013 to December 2018 in Ibn Sina medical college and hospital, Dhaka, Bangladesh with inclusion criteria. The weights of the newborns were measured without clothes on a digital weighing scale soon after the birth. Parameters such as birth weight, gender of baby, maternal age, parity and gestational age of the mother were noted. Data were analyzed statistically. Results: 52.99% baby was male and 47.01% were female. Low birth weight baby were 33.3% in the age group of less than 18 years of aged mother. With increasing the age of mother, birth weight of babies increase. Primipara mother delivered 15.52% low birth weight baby and 84.48% normal birth weight baby. With increasing parity birth weight of baby increased. The birth weight of <2.5 kg was 19.27% and 80.73% baby’s birth weight >2.5 kg in mother more than 37 weeks of gestation. Baby born by 35-37 weeks of gestation had 27.69% low birth weight and 72.31% were normal birth weight. Incidence of low birth weight was 79.3% and normal birth weight 20.7% found by 32-34 weeks of gestation. Bangladesh Journal of Medical Science Vol.19(2) 2020 p.291-295